Kawasan Titik Nol Kilometer Yogyakarta sebagai Ruang Publik dalam Perspektif Kritik Postkolonial - Diana Kurnia Putri (Departemen Ilmu Pemerintahan Fisip Unhas, 2019)
Yogyakarta City is known as a city with a rich cultural heritage of the meaning philosophy of life for its citizens. Zero Kilometer point area is the public space of the Yogyakarta city which is located in the center of Yogyakarta city. Public space is an important element that portrays an urban image as space for social interaction and becomes an icon of a city. This study aims to determine strategy of Yogyakarta city goverment in effort to arrangement region at Zero Kilometer point Yogyakarta as public space with analysis using post-colonial criticism theory. The research method used qualitative descriptive by explaining effort to arrange area at Zero Kilometer point by Yogyakarta goverment using post-colonial theory in the concept of mimicry. The analysis show that Zero Kilometer point area is a public space that contains a variety of activities that shape the social interaction of its users from various communities. In addition, the concept of regional arrangement at the Zero Kilometer Yogyakarta mimics the architecture style of Dutch colonial buildings.